2009
DOI: 10.1093/hmg/ddp394
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich repeat kinase 2 interacts with Parkin, DJ-1 and PINK-1 in a Drosophila melanogaster model of Parkinson's disease

Abstract: Mutations in the LRRK2 gene are the most common genetic cause of familial Parkinson's disease (PD). However, its physiological and pathological functions are unknown. Therefore, we generated several independent Drosophila lines carrying WT or mutant human LRRK2 (mutations in kinase, COR or LRR domains, resp.). Ectopic expression of WT or mutant LRRK2 in dopaminergic neurons caused their significant loss accompanied by complex age-dependent changes in locomotor activity. Overall, the ubiquitous expression of LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 29 publications
2
138
2
1
Order By: Relevance
“…Venderova et al (2009) report the genetic interaction between LRRK2 and PINK1 in Drosophila eyes. Consistently, mutant LRRK2 can activate pathologic JNK signaling via MAPKKs, and Parkin inhibits JNK in an E3 ligase activitydependent manner; these findings imply crosstalk between LRRK2 and PINK1 (Cha et al, 2005;Gloeckner et al, 2009;Hwang et al, 2010).…”
Section: Sir2 and Foxo As Novel Partners Of Pink1mentioning
confidence: 98%
“…Venderova et al (2009) report the genetic interaction between LRRK2 and PINK1 in Drosophila eyes. Consistently, mutant LRRK2 can activate pathologic JNK signaling via MAPKKs, and Parkin inhibits JNK in an E3 ligase activitydependent manner; these findings imply crosstalk between LRRK2 and PINK1 (Cha et al, 2005;Gloeckner et al, 2009;Hwang et al, 2010).…”
Section: Sir2 and Foxo As Novel Partners Of Pink1mentioning
confidence: 98%
“…In Drosophila, a dLRRK Y1383C mutant (analogous to human Y1699C) caused prominent vesicular aggregation of the protein and DA neuron loss [75]. Transgenic overexpression of human Y1699C or G2385R LRRK2 in Drosophila is also associated with DA neuron loss accompanied by locomotor deficits [117,122].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…Several reports suggested that LRRK2 interacts with Parkin, DJ-1 or PINK-1 in mammalian cell lines, C. elegans, and Drosophila melanogaster models of Parkinson's disease (82)(83)(84). Another recent study revealed that over-expression of LRRK2 accelerates the progression of neuropathological phenotypes in transgenic mice with the A53T α-synuclein mutation (85).…”
Section: Proteins Interacting With Lrrk2mentioning
confidence: 99%